2019
DOI: 10.1039/c8nj05248d
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent organotin compounds as dyes in silk fibroin (Bombyx mori): ultrasound-assisted synthesis, chemo-optical characterization, cytotoxicity, and confocal fluorescence microscopy

Abstract: The fluorescent silk fibroin (FSF) is useful in a number of biomedical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The values vary between 17 and 53% in CH 2 Cl 2 . The high quantum yields of 1 – 5 may be ascribed to the increase in molecular coplanarity which in turn reduces the number of nonradiative pathways , and also the presence of electron-donating groups in their ligand moieties such as −NEt 2 , −Me, and −OMe in case of 3 – 5 which favors the higher values (48–53%). , Previously it was reported that compounds with the nitro (−NO 2 ) group have low quantum yield as it withdraws electron density by inductive effect . However, in our case, 4 and 5 having a nitro group show good quantum yield; the reason for this may be the existence of the push–pull effect due to the presence of electron donor −NEt 2 ( 4 ) and −OMe ( 5 ) group which reduces the effect of the electron-withdrawing nitro group and helps in increasing the quantum yield .…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The values vary between 17 and 53% in CH 2 Cl 2 . The high quantum yields of 1 – 5 may be ascribed to the increase in molecular coplanarity which in turn reduces the number of nonradiative pathways , and also the presence of electron-donating groups in their ligand moieties such as −NEt 2 , −Me, and −OMe in case of 3 – 5 which favors the higher values (48–53%). , Previously it was reported that compounds with the nitro (−NO 2 ) group have low quantum yield as it withdraws electron density by inductive effect . However, in our case, 4 and 5 having a nitro group show good quantum yield; the reason for this may be the existence of the push–pull effect due to the presence of electron donor −NEt 2 ( 4 ) and −OMe ( 5 ) group which reduces the effect of the electron-withdrawing nitro group and helps in increasing the quantum yield .…”
Section: Results and Discussionmentioning
confidence: 99%
“…All the complexes exhibit an intense band in the visible region of the electronic spectra within a wavelength range of 459–482 nm (Figure a). This strong peak is attributed to highest occupied molecular orbital–lowest unoccupied molecular orbital electronic transition between n → π* which is mainly for the ligand-to-metal charge transfer (LMCT). ,,,, However, the band near 325–482 nm is due to the π → π* transition of intraligand charge transfer. ,,,, Moreover, the position of the λ max depends mainly on the electronic factors such as electron donor and electron-withdrawing groups attached to the molecule . The normalized UV–vis spectra of 1–5 are presented in Figure a.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to fabricate photoluminescent silk fibers, so far, three major strategies, that is, postfunctionalization, dietary modification, and genetic modification, have been developed. In the case of the postfunctionalization approach, various fluorescent materials including quantum dots (e.g., CdTe, ZnS, CdS, upconversion nanoparticles), organoboron complexes, Schiff compounds, organic molecules (e.g., 2,7-bis­[2-(4-nitrophenyl) ethenyl]-9,9-dibutylfl uorene, two-photon fluorophores), , and noble metal nanocluster (e.g., Au, Ag) , have been incorporated onto silk fibers by chemical or physical ways. However, it is inevitable to use toxic chemical substances and endure rigorous conditions in the process of incorporation.…”
Section: Introductionmentioning
confidence: 99%